Lung volume reduction surgery for ipsilateral emphysematous bullae after congenital diaphragmatic hernia repair - Alyssa E. Vaughn; Bailey D. Lyttle; Lauren T. Gallagher; Jason Gien; S Christopher Derderian; Kenneth W. Liechty (Elsevier, 2023)
Congenital diaphragmatic hernia (CDH) is characterized by a diaphragmatic defect with herniation of abdominal organs into the thoracic cavity. Outcomes are largely dependent on the degree of pulmonary hypoplasia and pulmonary hypertension, with the most severe cases associated with approximately 50% mortality. Long term pulmonary complications are well known, however, development of lobar emphysema leading to hemodynamic instability is exceedingly rare. We report the case of a patient with severe left-sided CDH who underwent successful diaphragmatic hernia repair but subsequently developed emphysematous bullous disease of the left lung with hemodynamic compromise, requiring emergent lung volume reduction surgery.